Avaliação da toxicidade de quantum dots de tamanhos mágicos de CdSe/CdS do tipo core shell no modelo animal C. elegans - Bastos, Victor Alexandre Félix (2016)
Magic-sized quantum dots (MSQD) are highly stable fluorescent nanocrystals with sizes < 2 nm, and remarkable optical and electronic properties. Since toxicity of cadmium composed quantum dots is highly controversial, our aim was to assess the effects of CdSe/CdS CS-MSQD on the animal model Caenorhabditis elegans (C. elegans), an important in vivo model for analysis of nanocompounds toxicity. We have exposed the nematodes to several concentrations of the MSQD, and evaluated the following endpoints: acute toxicity, life spam, growth, expression of stress related genes and bioaccumulation. The MSQD presented little to no toxicity, with a 24 h LC50 of 1815.039 g/mL while CdCl2 LC50 was 825.254 g/mL. MSQD exposed nematodes showed no significant difference in life spam or growth analysis. Furthermore, gene expression analysis of MSQD exposed nematodes demonstrated a diverse behavior from nematodes exposed to CdCl2. In addition, we could detect high stable fluorescence derived from MSQD within the exposed nematodes. Magic-sized (MSQDs) and ultra-small quantum dots (USQDs) are highly stable fluorescent nanocrystals with sizes < 2 nm, but differing on their unique optical and electronic properties. Because of their similar size, but different properties, our aim was to compare their effects on the embryonic development of Danio rerio (zebrafish), an important in vivo model for toxicity analyses. Both QDs were evaluated by optical absorption and fluorescence spectroscopy (FL), demonstrating that the MSQDs presented broader fluorescence spectrum than USQDs. We have exposed fertilized eggs of zebrafish to several concentrations of both QDs, and evaluated toxicity during embryonic development by observing anatomical and morphological changes. The CdSe/CdS CS-MSQDs presented higher toxicity than CdSe/CdS CS-USQDs at 10 μg/mL since larvae displayed abnormal development. The embryos did not hatch when cadmium chloride was applied in the same concentration (control). The CdSe/CdS CS-MSQD toxicity may be explained by the increasing concentration of Cd+2 ions on the surface, causing larger surface defects. The in vivo zebrafish model demonstrated to be an important tool for toxicity tests mainly caused by small variations on QDs nanostructures.